Shades of American Identity: Implicit Relations between Ethnic and National Identities. Issue 12 (December 2014) - Devos, Thierry; Mohamed, Hafsa
Abstract The issue of ethnic diversity and national identity in an immigrant nation such as the USA is a recurrent topic of debate. We review and integrate research examining the extent to which the American identity is implicitly granted or denied to members of different ethnic groups. Consistently, European Americans are implicitly conceived of as being more American than African, Asian, Latino, and even Native Americans. This implicit American = White effect emerges when explicit knowledge or perceptions point in the opposite direction. The propensity to deny the American identity to members of ethnic minorities is particularly pronounced when targets (individuals or groups) are construed through the lenses of ethnic identities. Implicit ethnic–national associations fluctuate as a function of perceivers' ethnic identity and political orientation, but also contextual or situational factors. The tendency to equate being American with being White accounts for the strength of national identification (among European Americans) and behavioral responses including hiring recommendations and voting intentions. The robust propensity to deny the American identity to ethnic minority groups reflects an exclusionary national identity.